Relapse occurrence in women with multiple sclerosis during pregnancy in the new treatment era. (6th March 2018) - Alroughani, Raed; Alowayesh, Maryam S.; Ahmed, Samar F.; Behbehani, Raed; Al-Hashel, Jasem
Abstract : Objective: To determine the rate of relapse occurrence during pregnancy and postpartum. Methods: In a cross-sectional study using the national multiple sclerosis (MS) registry, pregnant women with relapsing MS were identified. Data on demographics, clinical characteristics, and disease-modifying therapies (DMTs), including washout periods, were collected. Timings and durations of relapses were extracted. A multivariate logistic regression was used to assess the relationship between relapses and prior use of different DMTs. Results: Completed data were available for 99 pregnancies (87 patients). Mean age and mean age at onset were 31.8 ± 5 and 24.4 ± 5.6 years, respectively, while the mean disease duration was 7.4 ± 4.6 years. Most pregnancies (89.9%) occurred in patients who were on DMTs in the year preceding pregnancy with a mean treatment duration of 63.4 ± 29 months. The rates of occurrence of relapses during pregnancy and postpartum were 17.2% and 13.7%, respectively. Most of the relapses occurred during the first (n = 6) and third (n = 7) trimesters. Rate of relapse was highest among patients receiving natalizumab and fingolimod before pregnancy. A longer washout period was significantly associated with relapse occurrence. Conclusion: The relapse occurrence during pregnancy is higher than the previously published rates. The use of high-efficacy therapies with long washout periods before conception was associated with an increased risk of relapses during pregnancy. Postpartum relapse occurrence was similar to that in previous reports.